The Effect of Problem-based Learning Model on the Fourth-Grade Elementary Students' Learning Outcomes - Simare-Mare, Saguruh Melky Sedek; Silaban, Patri Janson; Gaol, Rumiris Lumban; Ambarwati, Nova Florentina; Abi, Antonius Remigius (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the effect of the problem-based learning model on students’ learning outcomes in theme 8 of the area where I live in class IV SD. The study in this paper uses associative quantitative methods. The research population involves 31 fourth-grade students at SD Negeri 065013 Tanjung Sari Medan. The sampling uses a purposive sample and there are 31 students. The results indicate that students’ learning outcomes using the problem-based learning model are included in the good category with an average of 78.19 with a correlation test result of 0.977, which means rcount 0.977 ≥ rtable 0.355, then Ha is accepted. Therefore, there is a significant effect between the use of the problem-based learning model on students’ learning outcomes on the theme of the area where I live in class IV SD Negeri 065013 Tanjung Sari Medan. It can be seen from the results of the T-test where tcount 24.598 ≥ ttable 2.045 so that Ha is accepted. As a result, there is a significant positive effect from the use of the problem-based learning model on student’s learning outcomes in theme 8 of the area where I live in class IV SD Negeri 065013 Tanjung Sari Medan in the academic year 2022/2023.